SOUND AND FAITH: RELIGIOUS COMMUNITY PRACTICE FOR THOUGHT MUSICAL COMPLEXITY SCHOLAR OF THE LAST QUARTER OF THE CENTURY XX - Postiga, José LuÃs (Cadernos de Educação Tecnologia e Sociedade, 2020)
When faced with the artistic-musical concepts developed in the second half of the twentieth century, it is common to observe them from the perspective of the scientific advances they have promoted or resulted from, the abstract organizations in which they are based, the aesthetic principles they create or and almost always fall within the individuality of the interpretation present in the creative act and its representativeness, regardless of the support in which it presents itself. Paradoxically, some of the main classical musical works written in the last quarter of the twentieth century resulted from the musicological study and/or musical representation of concepts, rites, religious practices representative of different cultures of the West and especially the East. In this sense, throughout the present article will be addressed works by composers of Western classical music, such as the case of Jonathan Harvey and Tristan Murail, characteristics of the musical currents that fit, from serialism to spectralism, as well as acoustic and electronic casts, which result. reinterpretations of religious practices of Hinduism and Buddhism, as well as sound behaviors of the communicative practice of peoples, such as the songs and instruments of Tibet and Mongolia.